PROFESSIONALISM OF ISLAMIC EDUCATION TEACHERS IN DEVELOPING CULTURE RELIGIUSITY OF MUSLIM STUDENTS IN SMK MUHAMMADIYAH MARAWOLA - Cika, Haer; Dihyah, Muhamad; Kahar, Iksan (Hunafa: Jurnal Studia Islamika, 2021)
This study aims to examine related problems: 1) What are the characteristics of the professionalism of Marawola Islamic religious education teachers in developing cultural religiosity at Muhammadiyah Vocational Schools? 2) How is the religiosity of Muslim students at Muhammadiyah Vocational School? The objectives of this study are: 1) To determine the characteristics of the professionalism of the Marawola Islamic religious education teachers in developing cultural religiosity at Muhammadiyah Vocational Schools. 2) To find out how the religiosity of Muslim students at Muhammadiyah Vocational High School. The results of this study indicate that Islamic religious education teachers are professional in carrying out their duties and responsibilities. Most of the students who attend SMK Muhammadiyah Marawola, seem to have quite good religiosity. There are several ways for Islamic religious education teachers at Muhammadiyah Marawola Vocational School in increasing the religiosity of Muslim students, namely by planning, implementing, and evaluating.